Designing a persuasive application for behaviour change with children: a design thinking approach - Mohd Mohadis, Hazwani; Mohamad Puad, Noor Hazwani; Rahim, Nurul Amirah; Ahmad Firdaus, Khadijah Hanis; Sayedi, Nawda (Readers Insight, 2020)
Persuasive technology is a technology that is designed deliberately to change user behaviour without coercion and deception. This study demonstrates the design of a persuasive mobile application aiming to encourage children below 12 years old to take care of their teeth and increase their awareness towards the importance of dental care. We applied a design thinking approach which comprised of five different phases: empathize, define, ideate, prototype, and test. A total of 13 children participated in this study. The findings show that children found that the application informs them how to brush their teeth properly and increases their awareness about the importance of dental care. This indicates that the design thinking approach is indeed useful for the designer to design a persuasive application aiming to change children’s behaviour